Association of adverse drug reaction to anti-tuberculosis medication with quality of life in patients in a tertiary referral hospital - Ronise Malaquias Carlos Valadares; Wânia da Silva Carvalho; Silvana Spíndola de Miranda (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: Adverse drug reactions can develop when using anti-tuberculosis medication, and the effects of the drugs can also significantly hinder the treatment of patients. METHODS: A cross-sectional survey was conducted in 73 patients using two standardized questionnaires and the World Health Organization Quality of Life-Bref. RESULTS: All patients reported the presence of adverse drug reactions, 71.6% of which are minor and 28.3% both major and minor. The global quality of life analysis showed that patients with tuberculosis have a good average (67.3%). CONCLUSIONS: There is an association between quality of life and adverse drug reaction, educational level, and vulnerability.